2012
DOI: 10.1590/s1809-29502012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Preferência podal em lactentes com síndrome de Down: fatores extrínsecos e intrínsecos

Abstract: RESUMO | Durante o processo de aquisição do chute em lactentes, a preferência podal pode ser influenciada de forma diferente pelos fatores extrínsecos e intrínsecos. O objetivo foi comparar a preferência podal e verificar a influência do peso adicional e do Reflexo Tônico Cervical Assimétrico (RTCA) na preferência podal entre lactentes com síndrome de Down e típicos. Participaram do estudo cinco lactentes com síndrome de Down e cinco típicos aos três e quatro meses de idade. O experimento foi subdividido em qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The awareness that there is a right and left side is also essential for the child to perceive its movement in time and space 25 . In a study that aimed to detect foot preference in children with Down syndrome, the researchers concluded that the difficulty in perceiving additional weight by the receptors present in the muscle spindles and tendons influences the formation of the body scheme and laterality 26 . The study compared a group with DS and another without DS in performing a task: moving a mobile with their feet, initially without a load and then with a load of one third of the weight of the legs.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness that there is a right and left side is also essential for the child to perceive its movement in time and space 25 . In a study that aimed to detect foot preference in children with Down syndrome, the researchers concluded that the difficulty in perceiving additional weight by the receptors present in the muscle spindles and tendons influences the formation of the body scheme and laterality 26 . The study compared a group with DS and another without DS in performing a task: moving a mobile with their feet, initially without a load and then with a load of one third of the weight of the legs.…”
Section: Discussionmentioning
confidence: 99%